How Job Stress and Job Satisfaction can Mediating Workload and Employee Performance at Badan Kepegawaian dan Pengembangan SDM (BKPSDM) of Melawi Regency, West Borneo - Ratu Loli Putri, Lekawati; Pranoto Hidayat, Anang; C. Iman Kalis, Maria; Daud, Ilzar; Sulistiowati, Sulistiowati (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2025)
The study examines how workload affects performance mediated by job stress and job satisfaction at BKPSDM employees of Melawi Regency, West Borneo. SPSS 22 and path analysis are used for data processing and analysis. While workload influences job stress and job satisfaction, it has no effect on employee performance. Similarly, job stress does not influence employee performance, but job satisfaction does. Workload also influences job satisfaction, which in turn influences employee performance. With an emphasis on lowering stress and raising job satisfaction, the study assists management in developing more effective workload management techniques. This can enhance worker performance when given more responsibilities, which affects the standard of public services and the effectiveness of the organization.